1982
DOI: 10.1088/0031-9155/27/6/001
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of age-dependent internal dose from radiopharmaceuticals

Abstract: The age-dependence of the radiation dose absorbed in a target organ or the total body is determined by the mass, size, shape and separation of the organs as well as by the metabolic behaviour of the radionuclide compound. Using values of the specific absorbed dose for adults, the age-dependent effective dose equivalents for 28 radiopharmaceuticals (62 radionuclides) were calculated by modifying the above mentioned values, considering radiation type, organ mass and source-target separation. From the results, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…As the risk of induction of radiogenic cancers at thyroid exposure to incorporated 131 I is strongly dependent on age at exposure and increases at young, age we study the quality of data on incidence for the age less than 30 years. As is shown in [12,14,15], for older age the thyroid dose is practically independent of age and determined by the amount of incorporated radionuclides only. The distribution functions for incidence ratios in this range and P values are presented in Figure 9 and Table 4.…”
Section: Methodology Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…As the risk of induction of radiogenic cancers at thyroid exposure to incorporated 131 I is strongly dependent on age at exposure and increases at young, age we study the quality of data on incidence for the age less than 30 years. As is shown in [12,14,15], for older age the thyroid dose is practically independent of age and determined by the amount of incorporated radionuclides only. The distribution functions for incidence ratios in this range and P values are presented in Figure 9 and Table 4.…”
Section: Methodology Of the Studymentioning
confidence: 99%
“…In [12,14,15] the relation of thyroid dose D and unit activity of incorporated 131 I has been derived as a function of age at the time of the Chernobyl accident. It has been shown that the difference in absorbed doses of younger age groups can occur earlier than at the age of 20-24 years at exposure.…”
Section: Methodology Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Effective half-life of radioiodide -The variability of the effective half-life of radioiodide is determined by the physical half-life of the isotope and its biological half-life (i.e., metabolic utilization and retention of organified iodide). Children and adolescents can be expected to exhibit higher turnover and elimination rates than adults (Rosenberg 1958;Heinrichs 1982;ICRP 1988). Dunning and Schwarz (1981) concluded that for adults, the observed range in biological halflives was from 21 to 372 days and for young children 4 to 39 days.…”
Section: -9 •mentioning
confidence: 99%
“…Für Kinder im Alter von einem halben Jahr wird die Exposition mit 4000 mGy/MBq angegeben, für Ein-jährige mit 3400, für Fünfjährige mit 1900 und für zehnjährige mit 1200 mGy/ MBq. Bei Fünfzehnjährigen liegt die Dosis mit 800 mGy/MBq noch doppelt so hoch wie bei Erwachsenen mit 400 mGy/MBq (19,20,26).…”
Section: Verringerung Des Karzinomrisikos Durch Stabiles Jodunclassified